Application of the AHP and VIKOR methods of individual decision making and the Borda method of group decision making when choosing the most efficient way of performing preparatory shooting at serial number one from a 12.7 mm long range rifle M-93 - Aleksić, Aleksandar R.; Delibašić, Boris V.; Jokić, Željko M.; Radovanović, Marko R. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The paper presents the method of applying multi-criteria decision-making methods in order to improve shooting and select the most favorable conditions for shooting. Alternatives were ranked by individual multi-criteria decision-making methods AHP and VIKOR by experts, and then the most favorable alternative was selected using the Borda method of group decision making. The aim of the work is to select the most efficient way of shooting with minimal human fatigue, consumption of movable things and in the shortest possible time through a combination of multi-criteria decision-making methods, which will ensure the accuracy and precision of the rifle for subsequent shooting and other operations. Methods: The paper presents one of the ways of using multidisciplinary methods of multi-criteria decision making for a specific problem in the field of tactics with weapon systems. Experts from the field of armaments, using the AHP and VIKOR methods of individual multi-criteria decision making, selected the most favorable alternative in accordance with four given criteria. Then, by applying the Borda method of group decision making, the the most favorable alternative was selected - the most favorable conditions for the execution of preparatory shooting at serial number one with a 12.7 mm long range rifle. The alternatives are four shootings, namely, two ways of performing preparatory shooting with a 12.7 mm long range rifle at serial number one, one from the current Instructions and Program of Shooting with Infantry Weapons and the other newly proposed method, as well as two ways of realizing shooting for testing the accuracy and precision of a long range rifle. Results: The selection of the most effective conditions for the execution of the first initial preparatory shooting at serial number one with a long range rifle, which will ensure maximum accuracy of the weapon and the minimum consumption of resources - time, ammunition, targets, and personnel fatigue. Conclusion: The solution takes into account the simultaneous optimization of several criteria in order to select the most efficient way of performing preparatory shooting at serial number one in order to ensure rested and trained personnel as well as accurate and precise long range rifles for subsequent shootings, which leads to the maximum saving of resources, the satisfaction of personnel, and precise weapons.
Keywords: long range rifle; rectification; shooting; AHP; VIKOR; Borda method